Investigations on graphene oxide for ion beam dosimetry applications. (August 2020) - Torrisi, L.; Silipigni, L.; Manno, D.; Serra, A.; Nassisi, V.; Cutroneo, M.; Torrisi, A.
Abstract: The oxygen content in graphene oxide (GO) can be reduced by the ion beam irradiation in high vacuum conditions. The reduction changes the C/O atomic ratio that increases with the absorbed ion dose. Moreover, as the level of reduction increases, the surface flattens and the material becomes denser. At high absorbed doses, greater than about 100 MGy, the material is affected by the high energy deposited with damage radiation effects which make the C/O ratio not proportional to the dose. At low doses, less than about 100 MGy, the C/O atomic ratio shows an optimal linearity with the ion dose and is independent of the ion stopping power, thus assuming the characteristics of a good biocompatible water-tissue equivalent dosimeter. The aim of the work was that to explore the possibility to use GO as ionizing radiation dosimeter for energetic ion beams by the measure of the compositional C/O atomic ratio. Highlights: Self-supported GO foils, 10 μm thick, with about 1 cm 2 surface can be employed as ion dosimeters. GO foils are reduced by the impact of ion beams at low and high stopping power. The GO level of reduction is measurable from the C/O atomic ratio. The C/O atomic ratio depends linearly with the absorbed dose in the range 1–100 MGy independently on the ion beam. The C/O atomic ratio growth exponentially for doses higher than 100 MGy and for ions at high stopping power.